Impact of Mindfulness and Coping Strategies on the Career Orientation among the University Students of Lahore, Pakistan - Mirza, Humira (Governance and Society Review, 2023)
Mindfulness can be a way to create an understanding of one’s self. The current study gives an insight into students who deploy coping strategies and mindfulness as prevailing techniques when they face difficulties along with the indication that can make them able to disengage or reengage from unattainable careers. Moreover, the research study adds to a growing body of research highlighting the relationship between mindfulness and coping strategies in terms of career orientation among university students in Lahore, Pakistan. For this purpose, a sample size of 377 students was gathered through a survey method. The responses were analyzed by using 25 versions of the Statistics Package for Social Sciences (SPSS). Usually, SPSS is used for measuring relationships by conducting a regression analysis, descriptive analysis, model summary, and ANOVA. The findings of this study reveal that mindfulness and coping strategies significantly impact career orientation without a doubt the more mindful students could be the more likely they are to disengage from failures or unattainable goals in making career decision and be hopeful about future. It suggests that mindfulness ability can improve the student goal adjustment abilities confronted challenges in future. So as to align their effects and drive themselves towards realistic goal As a result, mindfulness and coping strategies can be considered as key strategies towards building a successful career orientation. Additionally, these developmental strategies are recommended to the universities for a developed student career orientation.